RPC-Secret: Image Steganography Tool using Randomized GB-LSB and Parity Check - Tun, Wen Kit; Mohamad, Kamaruddin Malik (Applied Information Technology And Computer Science, 2023)
RPC-Secret: Image Steganography Tool using Randomized GB-LSB and Parity Check